The Malawi Communications Regulatory Authority: Issues of De Jure and De Facto Independence. Issue 2 (3rd April 2017) - Juwayeyi, Murendehle M.
Abstract : As independent regulatory agencies have been instituted to regulate disparate economic sectors in countries around the world, some research has focused on their independence vis-à-vis the governments in the countries, respectively, and vis-à-vis the various operators in the sectors they regulate in the countries. This article considers the formal and informal independence of the Malawi Communications Regulatory Authority from the government of Malawi, specifically focusing on the executive branch of government. It shows that the respective provisions in the Communications Act, 1998, that authorize the president to appoint members to serve on the Authority and authorize the roles that members of the executive branch of government have to play in the internal organization, administration, financial affairs, and regulatory activities of the Authority, cumulatively, undermine both the formal and informal independence of the authority. Further, the article contends that even the recent attempts to amend the law so as to enhance the independence of the Authority fall short. Moreover, the analysis herein has wider implications because this lack of independence is not unique to the Authority in Malawi but affects the respective communications regulators instituted by other countries in sub-Saharan Africa. Ultimately, the article offers possible ways to enhance the independence of the Authority and, by extension, these other regulators.